Myeloid-Specific Deletion of Epsins 1 and 2 Reduces Atherosclerosis by Preventing LRP-1 Downregulation. Issue 4 (15th February 2019) - Brophy, Megan L.; Dong, Yunzhou; Tao, Huan; Yancey, Patricia G.; Song, Kai; Zhang, Kun; Wen, Aiyun; Wu, Hao; Lee, Yang; Malovichko, Marina V.; Sithu, Srinivas D.; Wong, Scott; et al.
Abstract : Rationale: : Atherosclerosis is, in part, caused by immune and inflammatory cell infiltration into the vascular wall, leading to enhanced inflammation and lipid accumulation in the aortic endothelium. Understanding the molecular mechanisms underlying this disease is critical for the development of new therapies. Our recent studies demonstrate that epsins, a family of ubiquitin-binding endocytic adaptors, are critical regulators of atherogenicity. Given the fundamental contribution lesion macrophages make to fuel atherosclerosis, whether and how myeloid-specific epsins promote atherogenesis is an open and significant question. Objective: : We will determine the role of myeloid-specific epsins in regulating lesion macrophage function during atherosclerosis. Methods and Results: : We engineered myeloid cell–specific epsins double knockout mice (LysM-DKO) on an ApoE −/− background. On Western diet, these mice exhibited marked decrease in atherosclerotic lesion formation, diminished immune and inflammatory cell content in aortas, and reduced necrotic core content but increased smooth muscle cell content in aortic root sections. Epsins deficiency hindered foam cell formation and suppressed proinflammatory macrophage phenotype but increased efferocytosis and anti-inflammatory macrophage phenotype in primary macrophages. Mechanistically, we show that epsin loss specifically increased total and surface levels of LRP-1 (LDLR [low-density lipoprotein receptor]–related protein 1), an efferocytosis receptor with antiatherosclerotic properties. We further show that epsin and LRP-1 interact via epsin's ubiquitin-interacting motif domain. ox-LDL (oxidized LDL) treatment increased LRP-1 ubiquitination, subsequent binding to epsin, and its internalization from the cell surface, suggesting that epsins promote the ubiquitin-dependent internalization and downregulation of LRP-1. Crossing ApoE −/− /LysM-DKO mice onto an LRP-1 heterozygous background restored, in part, atherosclerosis, suggesting that epsin-mediated LRP-1 downregulation in macrophages plays a pivotal role in propelling atherogenesis. Conclusions: : Myeloid epsins promote atherogenesis by facilitating proinflammatory macrophage recruitment and inhibiting efferocytosis in part by downregulating LRP-1, implicating that targeting epsins in macrophages may serve as a novel therapeutic strategy to treat atherosclerosis. Abstract : Supplemental Digital Content is available in the text.